2009
DOI: 10.1016/j.bbrc.2009.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) as a key therapeutic trophic factor in bone marrow mesenchymal stem cell-mediated cardiac repair

Abstract: We recently demonstrated a novel effective therapeutic regimen for treating hamster heart failure based on injection of bone marrow mesenchymal stem cells (MSCs) or MSC-conditioned medium into the skeletal muscle. The work highlights an important cardiac repair mechanism mediated by the myriad of trophic factors derived from the injected MSCs and local musculature that can be explored for non-invasive stem cell therapy. While this therapeutic regimen provides the ultimate proof that MSC-based cardiac repair is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
63
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 41 publications
4
63
1
1
Order By: Relevance
“…PI3K catalytic subunit p110a and p110 are essential for cardiovascular differentiation upon treatment of EBs with VEGF As previously described, VEGF plays a crucial role in cardiac and vascular differentiation, and acts on Flk-1 + cardiovascular progenitor cells (Chen et al, 2006;Cheung, 1997;Gerber et al, 1998;Gliki et al, 2002;Song et al, 2007;Yang et al, 2002;Zisa et al, 2009;Lange et al, 2009). To investigate whether PI3K class IA isoforms are essential for VEGF signaling pathways leading to cardiac and vascular differentiation of ES cells, p110a, p110b and p110 gene-inactivated EBs were treated from day 4 to day 10 of cell culture with VEGF (500 pM).…”
Section: Pharmacological Inhibition Of Pi3ks and Targeting Of Class Imentioning
confidence: 78%
See 1 more Smart Citation
“…PI3K catalytic subunit p110a and p110 are essential for cardiovascular differentiation upon treatment of EBs with VEGF As previously described, VEGF plays a crucial role in cardiac and vascular differentiation, and acts on Flk-1 + cardiovascular progenitor cells (Chen et al, 2006;Cheung, 1997;Gerber et al, 1998;Gliki et al, 2002;Song et al, 2007;Yang et al, 2002;Zisa et al, 2009;Lange et al, 2009). To investigate whether PI3K class IA isoforms are essential for VEGF signaling pathways leading to cardiac and vascular differentiation of ES cells, p110a, p110b and p110 gene-inactivated EBs were treated from day 4 to day 10 of cell culture with VEGF (500 pM).…”
Section: Pharmacological Inhibition Of Pi3ks and Targeting Of Class Imentioning
confidence: 78%
“…Previous studies showed that VEGF is essential for cardiomyogenesis and/or vascular differentiation (Chen et al, 2006;Cheung, 1997;Gerber et al, 1998;Gliki et al, 2002;Song et al, 2007;Yang et al, 2002;Zisa et al, 2009;Lange et al, 2009;Bekhite et al, 2010) and might activate PI3K (Bos 1995;Gerber et al, 1998). Moreover, it has been suggested that Flk-1 + plays a crucial role in regulating PI3K activity in endothelial cells (Gerber et al, 1998;Ferrara, 1999;Thomas and Owen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The family of vascular endothelial growth factor (VEGF) molecules are potent initiators and regulators of angiogenesis with VEGF 165 being the most powerful and widely distributed within the body for promoting angiogenesis (Neufeld et al 1999;Zhao et al 2007). BMMSCs transfected with the VEGF gene have been used in the treatment of cardiovascular disease (Liu et al 2009;Pons et al 2009;Zisa et al 2009), bone regeneration , neurodegenerative , and Achilles tendon repair (Hou et al 2009). However, there has not been research on VEGF gene modified BMMSCs and its role in the liver disease process.…”
Section: Introductionmentioning
confidence: 99%
“…25 In our previous studies in the Syrian hamster with heart failure, we demonstrated the potential role of paracrine factors in mobilizing BMPCs after repetitive skeletal muscle injection of porcine MSCs, MSC media, and vascular endothelial growth factor. 24,26,52,53 The effects of single injections of MSC media in swine are controversial. 38,54 Some of the paracrine candidates secreted by porcine MSCs include vascular endothelial growth factor, insulin-like growth factor-1, and interleukin-6, and we Given the ability of CD133 ϩ BMPCs to coexpress cardiac lineage markers, including GATA-4, Nkx2.5, and troponin I, we propose that some of the myocyte proliferation that results from icMSCs reflects the transdifferentiation of endogenous BMPCs mobilized to the heart.…”
mentioning
confidence: 99%